Using Self-Monitoring of Performance With Self-Graphing to Increase Academic Productivity in Math. (August 2017) - Wells, Jenny C.; Sheehey, Patricia H.; Sheehey, Michael
Self-regulation skills have been found to be an important predictor of achievement in mathematics. Teaching a student to regulate his or her behavior during independent math work sessions using self-monitoring of performance with self-graphing focuses him or her on academic performance and results in increases in productivity and math proficiency. This article describes the process of designing and implementing this intervention.